A Simple and Ecofriendly One‐Pot Synthesis of Highly Substituted 3‐Cyanopyridine‐Quinoline Hybrids via a Triphenyphosphine‐Catalyzed Multicomponent Reaction Under Mild Conditions. (13th April 2016) - Ladraa, Souheila; Chioua, Mourad; Belfaitah, Ali
Abstract : Abstract : A simple and convenient one‐pot method has been used for the synthesis of new polycyclic compounds articulated around 3‐cyanopyridine derivatives from 2‐chloroquinolin‐3‐carbaldehydes, acetophenone derivatives, active methylene compounds, and ammonium acetate as a source of ammonia in the presence of catalytic amounts of PPh3 at room temperature. The salient features of the protocol used are mild reaction conditions, good yields, short reaction time, safety, and high atom economy. No column chromatographic was needed, and pure products were obtained by simple filtration and washing with Et2 O.